2010
DOI: 10.1037/a0019637
|View full text |Cite
|
Sign up to set email alerts
|

When goal orientations collide: Effects of learning and performance orientation on team adaptability in response to workload imbalance.

Abstract: The authors draw on resource allocation theory (Kanfer & Ackerman, 1989) to develop hypotheses regarding the conditions under which collective learning and performance orientation have interactive effects and the nature of those effects on teams' ability to adapt to a sudden and dramatic change in workload. Consistent with the theory, results of a laboratory study in which teams worked on a computerized, decision-making task over 3 performance trials revealed that learning and performance orientation had indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 41 publications
3
114
1
1
Order By: Relevance
“…The experience of excess resources, or slack, fuels experimentation and creativity (Nohria & Gulati, 1996). In contrast, experiencing resources as scarce challenges the ability to meet multiple goals (Kanfer & Ackerman, 1989;, intensifying their recognition of tensions between competing demands (Porter, Webb, & Gogus, 2010). Environmental conditions of plurality, change, and scarcity serve as boundaries that intensify the salience and engagement with paradox.…”
Section: Defining Paradoxmentioning
confidence: 99%
“…The experience of excess resources, or slack, fuels experimentation and creativity (Nohria & Gulati, 1996). In contrast, experiencing resources as scarce challenges the ability to meet multiple goals (Kanfer & Ackerman, 1989;, intensifying their recognition of tensions between competing demands (Porter, Webb, & Gogus, 2010). Environmental conditions of plurality, change, and scarcity serve as boundaries that intensify the salience and engagement with paradox.…”
Section: Defining Paradoxmentioning
confidence: 99%
“…Team performance orientation had a significant, positive relationship with team efficacy, although this relationship was weaker for those teams that received both individual and team feedback. Finally, a recent study by Porter, Webb, and Gogus (2010) examined the effects of team learning and performance orientation on the adaptive performance of teams performing a command and control simulation. The authors found that when teams had slack resources, team learning orientation led to performance improvements across the three trials, but team performance orientation only led to smaller improvements between the second and third performance trials.…”
Section: Goal Orientationmentioning
confidence: 99%
“…A large body of research has provided evidence of the important link between different individual achievement goal orientations and key outcome variables, such as work performance (Janssen & Van Yperen, 2004;Payne, Youngcourt, & Beaubien, 2007;Van Yperen, Elliot, & Anseel, 2009), feedbackseeking behavior (Porter, Webb, & Gogus, 2010;VandeWalle & Cummings, 1997), and helping behavior (Chiaburu, Marinova, & Lim, 2007).…”
Section: Introductionmentioning
confidence: 99%